(untitled) (Journal of Advanced Research in Social Sciences, 2022)
This paper aims to establish an association between black racial identity formation and the struggle to guarantee civil rights in Brazil. The consolidation of racial identity is a determining factor for the subject to become an active social agent, able to enjoy all their rights as a citizen. The introduction contextualizes matters involving identity formation in the colonial e imperial periods. Next, we examine the construction and consolidation of black identity from the legal abolition of slavery until the contemporary advances in the conquest of rights in Brazil. Finally, we observe that the consolidation of racial identity is directly linked to the organization and strengthening of Black Brazilian movement.